Executive attention and its relationship to psychological empowerment among faculty members in the Faculties of Physical Education and Sports Sciences - انور عبدالقادر ماشي (physical education and sport sciences college for women/ Baghdad University, 2021)
The research aims to know the executive attention and its relationship to psychological empowerment in the Faculties of Physical Education and Sports Sciences among the faculty members and in the variables of the study, the two researchers used the descriptive approach to suit it to the nature of the research. As for the research sample, it was represented by a group of male and female physical education teachers in four universities of (100) teaching staff And teaching The two researchers designed two measures (executive attention) and the scale (psychological empowerment) and distributed them to the sample electronically. The results were processed statistically through the Statistical Package Program (SPSS). The two researchers concluded that the teachers possessed the research sample both from executive attention and psychological empowerment. And its impact on shaping the student's personality and developing it through the educational media and publications